Islamic Education for Women Based On Buya Hamka and Murtadha Muthahhari’s Thoughts - Muhammad Rasyidil Fikri Alhijri; Amir Reza Kusuma; Ari Susanto; Mohammad Zakki Azani; Mohamad Ali (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Lack of knowledge and society awareness dealing with the importance of Women's Education often makes treat, differently between men and women in the teaching process. Even though both of them have different characteristics and needs. For this reason, the research will be discusse an effort to look deeper into some thoughts of women's education, developing women’s potential and maximising the potential of women as a support for the superior generation in civilization of ummah. This research is library research, while data obtained were analysed by using the documentary method. the researcher also use descriptive method, comparative method and content analysis method to analyzing data. This study found that: 1) according to Hamka the importance of women's education is because women play a very important role in life as a wife, a mother,an educator and a caregiver. 2) according to muthahhari women's education in Islam is important because it aims to make women understand about their duties and responsibilities in accordance with their nature as a wife and a mother who will educate their children later. 3) Both of them have an understanding of the importance on women education. While the different are in the way to understand the importance of women’s education. Hamka tend to understand it from interpreting Al-Qur’an and Al- Hadist, while Muthahhari tend to understand it from philosophical side.